Analisis Lipid Mikroalga Tetraselmi Chuii Dan Chlorella Vulgaris Sebagai Antioksidan - Aeni, Nur; Suprianti, Tuti (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
Microalgae have received attention as potential sources of bioactive compounds, especially lipids with antioxidant activity. This research aims to analyze the lipid content of the microalgae Tetraselmi Chuii and Chlorella Vulgaris and unlock their potential as antioxidant agents. The extraction method uses organic solvents namely olive oil followed by lipid composition analysis using gas chromatography techniques. Next, the antioxidant test was carried out using the in vitro method using DPPH (1,1-diphenyl-2-picrylhydrazyl). The analysis results show that the microalgae Tetraselmi Chuii and Chlorella Vulgaris contain various types of lipids, including omega-3 and omega-6 fatty acids which are known to have positive effects on health. Antioxidant tests showed that the lipid extracts of both microalgae showed significant antioxidant activity against DPPH free radicals. In particular, lipid compounds from Tetraselmi Chuii showed higher antioxidant effects compared to Chlorella Vulgaris. With antioxidant power of 83.77% and 83.61% respectively.